Factors of Medicinal Plants Users as Alternative Medicinal in Indonesia - Yunita Theresiana; Kamaluddin Kamaluddin; Sriati Sriati; Lili Erina (Science and Technology Indonesia, 2018)
Traditional medicines are the cultural heritance of Indonesian nation that should be preserved and developed in order to support the society’s health development and to improve the society’s economy. This research was aimed to figure out the society’s behaviors in using traditional medicines and the dominant factors that influence them in using traditional medicines. This research is a non-experimental research, with analytical survey method and cross-sectional approach. Fifty percent of the existing districts (16 districts) were selected randomly to serve as the sample. The districts selected included the districts of Muara Kuang, Tj. Raja, Lubuk Keliat, Payaraman, Indralaya, Pemulutan, Pemulutan Selatan and Rantau Panjang, totaling eight. The number of villages selected was 66. From these villages, the research sample was selected using stratified random sampling technique, and a sample of 400 people was obtained. The analysis was conducted in a bivariate manner with chi square test. The results showed that the respondents were motivated to use traditional medicines through (a) predisposing factors perceived sickness; (b) enabling factors, including economic level, location of domicile, type of complaints, insurance and distance to health facilities; and (c) reinforcing factors, including family support and traditional medicine promotion. Serving as the predicting factors in the traditional medicine use were the variables perceived sickness, type of complaint, distance to health facilities and traditional medicine promotion, with the variables occupation, insurance, education, family support, domicile and income serving as the confounding variables.